IMPLEMENTATION OF GAGNE’S THEORY ON MATHEMATICS LEARNING OUTCOMES - Ayuni, Abelia; Maharani, Anggita (Cirebon International Conference on Education and Economics Proceeding, 2024)
This research aims to help us understand the learning process that occurs within children. Its application in learning addition and subtraction in 7 year old children. This research uses a descriptive method, namely describing or explaining variables in the field based on a literature review. Data regarding learning outcomes in addition and subtraction material for children aged 7 years as a research sample were obtained through questions. Remembering the concepts that will be studied such as addition is used to add the number of numbers with numbers, and subtraction to subtract the number of numbers with numbers. The researcher gave 5 candies and gave the child a question, he had to do the question correctly and precisely, if he was wrong then the candy would be deducted. So the results of this research show that there is an influence of the application of learning using Gagne’s theory on the learning outcomes of 7 year old children.